PERANCANGAN SISTEM PRESENSI BERBASIS WEB MENGGUNAKAN ALGORITMA HAVERSINE PADA PT MITRA PERKASA EKATAMA - Isma Raudhatul Janah; Dani Yusuf; Siti Setiawati; Hendarman Lubis (Journal of Information System, Applied, Management, Accounting and Research, 2026)
The development of information technology encourages companies to implement digital systems to support administrative management, including employee attendance processes. PT Mitra Perkasa Ekatama still uses fingerprint machines that have limitations in monitoring the attendance of employees who work outside the office or project locations and do not yet support attendance location validation. This study aims to design a web-based employee attendance system by implementing the Haversine Algorithm as a method for calculating the distance between the user's location and the company's location to validate attendance. The system development method used is Waterfall which includes the stages of planning, needs analysis, design, implementation, testing, implementation, and system maintenance. The system was built using PHP, HTML, CSS, JavaScript, MySQL, and utilizes Global Positioning System (GPS) technology. The Haversine Algorithm is used to calculate the distance based on latitude and longitude coordinates so that the system can determine whether the user is within the permitted attendance radius. The results of the study show that the system successfully integrates login features, employee data management, positions, departments, attendance entry, attendance departure, permit applications, leave applications, and attendance recapitulation in one web-based application. Testing using the Black Box Testing method shows that all system functions run well with a success rate of 100%. The resulting system is able to help companies in automatically validating attendance locations and improving the management of employee attendance data in an integrated manner